Broken Instrument Removal Methods with a Minireview of the Literature - Mohsen Aminsobhani; Nasim Hashemi; Fatemeh Hamidzadeh; Pegah Sarraf (Case Reports in Dentistry)
Instrument fracture in the root canal system is an unpleasant incident that may occur during root canal treatment. Comprehensive cleaning of the root canal system is often impossible in the presence of a broken instrument. Therefore, it is often imperative to remove the broken fragment from the root canal system. To date, various methods have been proposed for the removal of broken instruments from the root canal system. However, no consensus has been reached on a safe technique with a high success rate for broken instrument removal. This case series reports six cases of successful removal of broken instruments using different methods including the ultrasonic, tube-and-glue, tube-and-wire, tube-and-internal shaft, and the forceps techniques and also provides a brief review of the relevant literature.